Explaining forest productivity using tree functional traits and phylogenetic information: two sides of the same coin over evolutionary scale?. Issue 9 (27th March 2015) - Paquette, Alain; Joly, Simon; Messier, Christian
<x xml:space="preserve">Abstract</x> The importance of biodiversity for ecosystem functioning and for the provisioning of services to humanity is well established. Yet we still are looking for methods to quantify this biodiversity that are both relevant and efficient. Here we show that phylogenetic information can help, especially when key functional traits are unavailable, and how it relates to functional traits of species.